2022
DOI: 10.1187/cbe.21-05-0127
|View full text |Cite
|
Sign up to set email alerts
|

A Revised Measure of Acceptance of the Theory of Evolution: Introducing the MATE 2.0

Abstract: An updated version of the most popular survey used to measure student evolution acceptance in education studies, the Measure of Acceptance of the Theory of Evolution (MATE), is provided. Process, structural, and concurrent validity evidence for the new measure, the MATE 2.0, are supplied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In particular, the acceptance of evolution within the scientific community is often accepted by German creationists (Beniermann, 2019); hence, it may fail to be a good indicator for evolution acceptance for this group. Additionally, Barnes and colleagues (2022a) demonstrated that these two items are problematic not only because of the potential acceptance of creationists but also due to uncertainty about the standpoint of the scientific community by the test taker. The evidence for evolutionary theory may be an ambivalent measure for evolution acceptance because creationists in the German context claim that data can be interpreted in different ways, i.e., evolution or creation (Junker & Scherer, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the acceptance of evolution within the scientific community is often accepted by German creationists (Beniermann, 2019); hence, it may fail to be a good indicator for evolution acceptance for this group. Additionally, Barnes and colleagues (2022a) demonstrated that these two items are problematic not only because of the potential acceptance of creationists but also due to uncertainty about the standpoint of the scientific community by the test taker. The evidence for evolutionary theory may be an ambivalent measure for evolution acceptance because creationists in the German context claim that data can be interpreted in different ways, i.e., evolution or creation (Junker & Scherer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the two MATE scales was also identified in previous studies based on correlations with results derived from the GAENE (Metzger et al, 2018; Sbeglia & Nehm, 2018). One reason may be that the scale MATE credibility includes several items for which measuring issues have been suggested, like the mixture of questions on evolution acceptance and religious belief (MATE_14R; Smith et al, 2016; Sya'bandari et al, 2021) or the general reputation of the theory of evolution in the scientific community (MATE_5R and MATE_17R; Barnes et al, 2022a; Beniermann, 2019). This could be a particular problem when addressing creationist samples.…”
Section: Discussionmentioning
confidence: 99%
“…Item G79 ("Humans are descended from other primate species") was based on the well-known instrument “MATE”, keeping the same wording in the revised version [ 8 ] for the statement about humans, revealing difficulties of evolution in 34 countries [ 2 ]. Many studies have shown that when the human species is concerned, opinions about evolution tend to be extreme, with some people considering evolution for all organisms except our species [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of different instruments to measure evolution acceptance could be a cause of conflicting research results. A variety of tests have been proposed, including the Measure of Acceptance of the Theory of Evolution (MATE), which has been widely used for more than 20 years and recently revised [ 8 ], the Inventory of Student Evolution Acceptance (I-SEA) [ 9 ], the Generalized Acceptance of EvolutioN Evaluation (GAENE) [ 10 ], etc. It should be considered that the studies cited above differ in their contexts of comparison in relation to ages, countries, and socioeconomic levels, as well as the number of data collected and measurement statistics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation